The Validity of Demonstration-Based Audio-Visual Learning Media on The Topic of Temperature, Heat and Its Displacement in Fifth Grade - Ningratih, Sang Ayu Nyoman; Astawan, I Gede; Margunayasa, I Gede (Universitas Pendidikan Ganesha, 2021)
The online learning process tends to make students' responses less active. Therefore it requires learning media that can play an active role in explaining the material, such as audiovisuals. The purpose of this study was to produce valid demonstration-based audio-visual learning media on the topic of temperature, heat, and its displacement in the fifth grade. The model used is the 4D model, which consists of defining, designing, developing, and disseminating. The subject of the trial was conducted on two material experts, two media experts, and two practitioners. The data collected are qualitative data and quantitative data. Data collection was carried out using a questionnaire method. Data were analyzed using the mean formula to determine the average media validity score. The average validity score of demonstration-based audiovisual learning media in terms of material experts is 3.92, with very good qualifications. In terms of media experts of 3.80 with very good qualifications. In terms of practitioners, it is 3.87 with very good qualifications. It shows that the demonstration-based audio-visual learning media on temperature, heat, and its displacement in fifth grade are deemed appropriate for use in the learning process.